1998
DOI: 10.1128/jcm.36.2.367-374.1998
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Differentiation of Closely Related Candida Species and Strains by Pyrolysis-Mass Spectrometry and Fourier Transform-Infrared Spectroscopy

Abstract: Two rapid spectroscopic approaches for whole-organism fingerprinting of pyrolysis-mass spectrometry (PyMS) and Fourier transform-infrared spectroscopy (FT-IR) were used to analyze a group of 29 clinical and reference Candida isolates. These strains had been identified by conventional means as belonging to one of the three species Candida albicans, C. dubliniensis(previously reported as atypical C. albicans), and C. stellatoidea (which is also closely related to C. albicans). To observe the relationships of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
0
8

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 182 publications
(94 citation statements)
references
References 35 publications
3
83
0
8
Order By: Relevance
“…This 'holistic' approach allows highthroughput, unbiased examination of sample biochemistry and, through suitable interpretation, can be used to monitor plant responses to abiotic or biotic influences (Goodacre et al, 1998). Previous work on food quality (Lai et al, 1994;Goodacre & Anklam, 2001;Ellis et al, 2002), bacterial and fungal species (Helm et al, 1991;Goodacre et al, 1998;Timmins et al, 1998), and plant systems (Gidman et al, 2003;Johnson et al, 2003), including those subjected to N application (Gidman et al, 2004(Gidman et al, , 2005, has already indicated the potential of this approach.…”
Section: Methodsmentioning
confidence: 99%
“…This 'holistic' approach allows highthroughput, unbiased examination of sample biochemistry and, through suitable interpretation, can be used to monitor plant responses to abiotic or biotic influences (Goodacre et al, 1998). Previous work on food quality (Lai et al, 1994;Goodacre & Anklam, 2001;Ellis et al, 2002), bacterial and fungal species (Helm et al, 1991;Goodacre et al, 1998;Timmins et al, 1998), and plant systems (Gidman et al, 2003;Johnson et al, 2003), including those subjected to N application (Gidman et al, 2004(Gidman et al, , 2005, has already indicated the potential of this approach.…”
Section: Methodsmentioning
confidence: 99%
“…62 Whole organism fingerprinting Recent developments in analytical instruments have made the rapid, automated and accurate identification of clinical yeast possible without the need for extensive sample preparation. 66 Physiochemical spectroscopic methods such as pyrolysis-mass spectrometry, Fourier transform-infrared spectroscopy and UV resonance Raman spectroscopy allows for the direct analyses of samples and provides so called whole organism fingerprints which is a phenotypic measure of the physiochemical composition of the organism. It must, however, be noted that other sources of chemical variation in biological samples, such as media composition and colony size should be minimised to obtain standardised spectra for each organism.…”
Section: Protein Fingerprintingmentioning
confidence: 99%
“…67 Pyrolysis-mass spectrometry has been used successfully in the identification of clinically relevant bacteria and involves the thermal degradation of the sample and the production of volatile molecular fragments. 66 These fragments are analysed using a mass-spectrometer, yielding a mass spectrum which measures the strengths of covalent bonds between the molecules of the organism. It was found that the mass spectra of C. dubliniensis and C. albicans showed little qualitative differences, but quantitative differences between the spectra could be observed.…”
Section: Protein Fingerprintingmentioning
confidence: 99%
See 1 more Smart Citation
“…1 and 2 respectively. The cluster analysis process is based on that developed by Gutteridge et al [12] to analysis PyMS data, and has been adapted in-house for the analyses of high dimensional infrared [13] and Raman spectra [14]. Brie£y, the initial stage involved the reduction of the dimensionality of the ESI-MS data by principal components analysis (PCA) [15].…”
Section: Electrospray Ionisation Mass Spectrometrymentioning
confidence: 99%